The Relationship between Work Culture and Work Behaviours: a Cross-cultural Study - Tadeusz Borkowski; Murat Çolak (Jesuit University Ignatianum in Krakow, 2015)
The paper presents an analysis of the research into the influence of culture differences on behaviour at work and the interactions between attitudes and behaviours at work on the example of Turkey and Poland. In order to examine this problem a model of work culture was developed. The study involved altogether 583 production workers. The results indicated a strong relationship between work culture and attitudes at work (e.g. the significance of work for the worker, engagement, self-discipline, effort invested in work) as well as behaviours at work (e.g. effectiveness, competence, absence, sick leaves).   Związek między kulturą pracy a zachowaniami w pracy: badania międzykulturowe. Artykuł przedstawia analizę wyników badań dotyczących różnic kulturowych w zachowaniu w pracy oraz interakcji pomiędzy postawami i zachowaniami w pracy na przykładzie Turcji i Polski. W celu zbadania powyższej kwestii utworzony został model kultury pacy. W badaniach wzięło udział łącznie 583 pracowników produkcyjnych. Wyniki badań wskazały na silny związek między kulturą pracy a postawami w pracy (np. znaczenie pracy dla pracownika, zaangażowanie, zdyscyplinowanie, wysiłek włożony w pracę) oraz zachowaniami w pracy (np. efektywność, sprawność, absencja, zwolnienia z pracy).